Respuesta :

Answer:

[tex]\frac{7x}{8}-\frac{1}{40}[/tex]

Step-by-step explanation:

[tex](\frac{3x}{4}-\frac{5}{8})+(\frac{x}{8}+\frac{3}{5})[/tex]

By combining the like terms,

= [tex](\frac{3x}{4}+\frac{x}{8})+(\frac{3}{5}-\frac{5}{8})[/tex]

= [tex](\frac{6x}{8}+\frac{x}{8})+(\frac{3}{5}\times \frac{8}{8}-\frac{5}{8}\times \frac{5}{5} )[/tex]

= [tex]\frac{7x}{8}+(\frac{24}{40}-\frac{25}{40})[/tex]

= [tex]\frac{7x}{8}-\frac{1}{40}[/tex]

Therefore, by solving the given expression we find the answer as [tex]\frac{7x}{8}-\frac{1}{40}[/tex].